Proposed new interior design scheme of Casa D' Rias Beauty Centre at 164, Jalan Maarof, Bukit Bandaraya, Bangsar, 59000, Wilayah Persekutuan Kuala Lumpur for Casa D' Rias / Iskandar Al-Haziq Ahmad Nazri - Ahmad Nazri, Iskandar Al-Haziq (Faculty of Architecture, Planning and Surveying, 2012)
By proposing this project of new interior designs scheme for Casa D’ Rias Beauty Centre, it marks a significant of delivering something very close and personal to myself. The main objective of this project is to proposed new interior design scheme for Casa D’ Rias Beauty Centre as a one-stop-beauty-centre that caters the modern hectic lifestyle of those women in Malaysia. This project is also to develop a design scheme that would define and refine the corporate image and identity of Casa D’ Rias itself in the beauty industry in Malaysia. It is a challenge to design a one stop beauty centre to cater all the services and reach the expectation of the atmosphere from the beauty centre itself. This requires an active thinking skill of combining practicality with the sense of beauty. Besides that, this project also offers a comprehensive range of facilities and professional services which are rendered according to the guideline set-up by the client itself. In order to help me in design, several interviews and observations had been made and conducted to collect relevant technical data and information for instance, my survey forms which is also featured in the appendixes section of this report writing. Based on my case studies and understanding of the project, we can conclude that it is important and crucial to create a useful space in one beauty centre that serves its purpose as a place to destress the stress by the customers. Besides that, a good interior space can be used to define one corporate image and identity while the business is operating.